Cancer patient perspective in the arena of COVID‐19 pandemic. Issue 1 (19th August 2021) - Ballatore, Zelmira; Merloni, Filippo; Ranallo, Nicoletta; Bastianelli, Lucia; Vitarelli, Francesca; Cantini, Luca; Ricci, Giulia; Ferretti, Benedetta; Alessandroni, Paolo; Del Prete, Michela; Chiorrini, Silvia; Safi, Mobin; et al.
Abstract: Objective: The coronavirus disease 2019 (COVID‐19) outbreak has been declared a global pandemic of unprecedented proportions. Italy is a country which has been heavily affected. Cancer patients are at a higher risk owing to their intrinsic fragility related to their underlying disease and oncologic treatment. Against this backdrop, we conducted a survey to investigate how patients perceived their condition, clinical management and availability of information during the pandemic. Methods: Between 15 April and 1 May 2020 a survey was submitted to cancer patients at oncology departments in the Marche region. Questions regarding the perception of personal safety, continuity of cancer care, information quality and psychological distress. Results: Seven hundred patients participated in the survey; 59% were female and 40% were aged between 46 and 65. The majority of the participants perceived compliance with appropriate safety standards by cancer care providers and 80% were reassured about their concerns during the medical interview. 40% were worried of being at a higher risk of infection and 71% felt they were at a greater risk because of chemotherapy. 55% felt that postponing cancer treatment could reduce its efficacy, however 76% declared they did not feel abandoned at the time of treatment postponement. Patients between 46 and 65 years declared a significant reduction in sleep ( p  < 0.01) and in concentration ( p  = 0.03). Conclusions: The emergency care offered to cancer patients has been deemed satisfactory in terms of both safety standards and care management. However, the majority of participants perceived the mutual negative influence between their oncologic disease and the risk of infection highlighting the need for special measures to ensure safe continuity of care.